2019
DOI: 10.1038/s41598-019-42633-9
|View full text |Cite
|
Sign up to set email alerts
|

Selenium nanoparticles for targeted stroke therapy through modulation of inflammatory and metabolic signaling

Abstract: Ischemic cerebral stroke is a major cause of death and morbidity. Currently, no neuroprotective agents have been shown to impact the clinical outcomes in cerebral stroke cases. Here, we report therapeutic effects of Se nanoparticles on ischemic stroke in a murine model. Anti-transferrin receptor monoclonal antibody (OX26)-PEGylated Se nanoparticles (OX26-PEG-Se NPs) were designed and synthesized and their neuroprotective effects were measured using in vitro and in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
138
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 224 publications
(151 citation statements)
references
References 58 publications
0
138
0
2
Order By: Relevance
“…On the other hand, selenium‐based nanoparticles (SeNPs) have shown to have similar or even higher beneficial effect compared to Se‐based compounds, but with lower toxicity . Several authors have reported interesting results concerning the use of SeNPs as a therapeutic agent for neurodegenerative diseases . Several works demonstrated that SeNPs are able to reduce Aβ aggregation and prevent Aβ‐induced toxicity in PC12 cells .…”
Section: Inorganic Nano‐antioxidants For Biomedical Applicationsmentioning
confidence: 99%
“…On the other hand, selenium‐based nanoparticles (SeNPs) have shown to have similar or even higher beneficial effect compared to Se‐based compounds, but with lower toxicity . Several authors have reported interesting results concerning the use of SeNPs as a therapeutic agent for neurodegenerative diseases . Several works demonstrated that SeNPs are able to reduce Aβ aggregation and prevent Aβ‐induced toxicity in PC12 cells .…”
Section: Inorganic Nano‐antioxidants For Biomedical Applicationsmentioning
confidence: 99%
“…Various tissues or organs in the human body undergo degeneration or loss due to trauma, disease, and aging . The improved understanding of natural tissue healing processes and function has encouraged the scientific community to search for new regenerative approaches such as tissue engineering, which provides potential solutions for regenerating the damaged tissues .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the administration of biodegradable selenium (Se) nanoparticles led to the protection of axons in the hippocampus region and myelination of the hippocampal area after cerebral ischemic stroke. Mechanically, Se administration suppressed excessive inflammation and oxidative metabolism, and Hippo signaling was shown to be involved in this process (39).…”
Section: Role Of Hippo Signaling In Neuronal System Diseasesmentioning
confidence: 99%